The Implementation of Islamic Counseling for Students' Mental Development in Madrasah - Hasibuan, Herdiansyah; Lubis, Saiful Akhyar; Budianti, Yusnaili (Jurnal Basicedu, 2022)
This study aims to describe the implementation of Islamic counseling (BK) for students' mental development at the Tanjung Balai City Madrasah. This type of research is a qualitative category with a descriptive study method. Data collection techniques using interviews, observation, and document review. Then the data were analyzed by data reduction steps, data exposure, and drawing conclusions. In this case, the data were checked by using credibility, dependability, confirmability, and transferability techniques. The results of this study indicate that BK services at the Tanjung Balai City Madrasah in an effort to develop students' mentality are carried out well. This is indicated by (1) Islamic BK activity programs and mental development of students covering the fields of faith, morals, worship, and muamalah; (2) stages of Islamic BK services in students' mental development, namely case identification, diagnosis, prognosis, therapy, evaluation, and follow-up; (3) Islamic counseling services have an impact in the form of students' ability to adapt at school and in the community; (4) assisting students in self-control when socializing. Likewise, there are several obstacles in the implementation of Islamic BK in the mental development of students, namely the minimum ratio of BK teachers compared to students in madrasas and limited BK service facilities. The solutions offered are the massive efforts of BK teachers to participate in offline and online training and the provision of BK facilities in madrasah.